Study of Financial Literacy, Financial Self-Efficacy and Financial Behavior: A Two Stage Mediation Mechanism of Financial Socialization - Maitlo, Ayaz Ali; Bhutto, Sarfaraz Ahmed; Brohi, Humair Athar; Dootio, Lareb Nisar; Muqadas Siyal (JISR management and social sciences & economics, 2025)
Locally in Sindh, Pakistan, financial socialization influences in the relationship between behavior, self-efficacy and literacy are lacking attention, hence the saving and investment is not recorded at better level. This study has used cross-sectional quantitative research design along with the positivist research philosophy and deductive research approach. Statistically, the research has used descriptive analysis and regression models of two-stage mediation analysis. The targeted respondents are N= 141 individuals of educational institutions from Larkana participated in this survey. After the analysis the findings reflect that there is a mediation of financial socialization in relationship between financial literacy, self-efficacy and behavior. In addition, direct relationship is significant and positive in financial literacy, self-efficacy and behavior. Indirect results achieved with partial mediation of financial socialization in between financial literacy and behavior as well financial self-efficacy and behavior. Hence these results highlight how these factors are interconnected in influencing financial decision-making, which is consistent with other studies on the value of social influences, psychological characteristics, and education in enhancing financial results. The outcomes of this study are recommended for policy makers in both public and private sectors and managerial personnel of financial institutions.